THE INFLUENCE OF ENGLISH AS A MEANS OF INTERCULTURAL COMMUNICATION: ITS IMPACT ON NATIONALISM AND CULTURAL CONSCIOUSNESS - Sinaga, Jelita Novrianti; Nabila, Sayra; Banjarnahor, Yunlis Y; Tindaon, Marshanda (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2023)
In the era of globalization and advances in information technology, the use of English is becoming an increasingly common phenomenon in many countries. English is often used in everyday communication, in the media, in the entertainment industry, and in the business sector. This phenomenon has sparked widespread debate about the social and cultural implications of the onslaught of English language use. English has a significant influence on nationalism and cultural awareness in Indonesia. The use of English as an international language can help Indonesians keep up with scientific developments and compete with other countries. However, the use of foreign languages can also lead to the loss of Indonesian identity as a language of national pride. This research aims to analyze the influence and impact of English as an Intercultural Communication Tool. In writing this scientific article using the literature review research method or literature study is the existence of a collection of theories related to the research problems carried out by researchers. As it is known that Globalization is currently very fast, of course there will be an impact in the future on all aspects of life. Such influences will be seen in the fields of education, and culture, and have an impact on nationalism awareness. Therefore, it is necessary to take action to prevent unwanted threats to Indonesian nationalism and culture. To address the phenomenon of the widespread use of English, a balanced approach is needed between the needs of global communication and the interests of maintaining national culture and identity. There is a need to raise awareness about the social, cultural, and economic significance of English language use so that people can make informed decisions about the potential use of English while strengthening their national identity and mother tongue.